2001
DOI: 10.1016/s0165-2370(00)00181-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of impregnation by hydrocarbons on coal structure during its thermal evolution

Abstract: The present work analyses the changes in the chemical structure of a perhydrous coal during its thermal evolution at different temperatures in an open-medium pyrolysis system. The results obtained were compared with those described for non-perhydrous coals in order to establish the effect of the substances assimilated by the coal structure (hydrocarbon/oil-like substances) on the thermal evolution of the coal. The transformation ratio at each stage of thermal treatment was determined and the chemical-structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…In the studied coals, micrinite ( fluorescence, probably due to either higher hydrogen content or different precursor material which shows suppressed reflectance (VRr=0.9%) (Perrussel et al, 1999;Iglesias et al, 2001).…”
Section: Coaly Faciesmentioning
confidence: 99%
“…In the studied coals, micrinite ( fluorescence, probably due to either higher hydrogen content or different precursor material which shows suppressed reflectance (VRr=0.9%) (Perrussel et al, 1999;Iglesias et al, 2001).…”
Section: Coaly Faciesmentioning
confidence: 99%
“…Since many of the vitrinite macerals in the Upper Medicine River Seam fluoresce, vitrinite reflectance values are likely suppressed, as has been demonstrated for the Mannville coals . Suppression has been attributed to: (1) the impregnation of the vitrinitic matrix by bitumen generated under severe bacterial activity; and (2) the incorporation into the vitrinite structure of lipids derived from bacteria cell walls themselves ( [Veld and Fermont, 1990], [Rathbone and Davis, 1993], , [Suarez-Ruiz et al, 1994], [Perrussel et al, 1999] and [Iglesias et al, 2001]). …”
Section: Gas Content and Saturationmentioning
confidence: 99%
“…Thus, natural evolution can be considered as a peculiar kind of pyrolysis which normally occurs at low temperatures (<200 8C) over millions of years. For this reason, different pyrolysis experiments were used to obtain valuable information about the phenomena that occur during natural evolution [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis 77 (2006) [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191] Whereas vitrinites are generally gas-prone materials, perhydrous vitrinites have the potential to generate liquid products [10]. Upon Gray-King pyrolysis they yield much more oil than non-perhydrous vitrinites [11] and they show a very high petroleum potential and low thermostability [12][13][14][15]. Thermogravimetric studies on hydrogen-rich vitrinites [14,16] have shown that their thermal behaviour is similar to that of type I kerogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation